2008
DOI: 10.1021/la800967x
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Assembly of UV-Resistant Poly(3,4-ethylenedioxythiophene) Thin Films

Abstract: The layer-by-layer assembly technique was used to create electrically conductive films with poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) (PEDOT-PSS) and branched polyethylenimine (BPEI). Titanium dioxide (TiO(2)) and carbon black were used to prevent UV-degradation of these PEDOT-PSS thin film assemblies. Film growth and conductivity were studied, while varying composition and examining the effect of UV absorbing particles on the electrical conductivity. All films showed similar initial sheet resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…trolyte multilayers with preformed titania nanoparticles [38,39] or with a titania precursor, titanium(V) bis(ammonium lactato) dihydroxyide (TIBALDH), followed by thermal treatment for the formation of tubular titania nanotubes, [40] hollow titania nanoparticles, [41,42] or titania shells. [43] CBD [36] and SAM [37] methods involve adsorption of TiO 2 from colloid suspensions and subsequent annealing with the solid substrates at 60 or 80 8C, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…trolyte multilayers with preformed titania nanoparticles [38,39] or with a titania precursor, titanium(V) bis(ammonium lactato) dihydroxyide (TIBALDH), followed by thermal treatment for the formation of tubular titania nanotubes, [40] hollow titania nanoparticles, [41,42] or titania shells. [43] CBD [36] and SAM [37] methods involve adsorption of TiO 2 from colloid suspensions and subsequent annealing with the solid substrates at 60 or 80 8C, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…H. Fu, Ji, Yuan, & Shen, 2005;J. Fu, Ji, Fan, & Shen, 2006), anti-reflection (Hiller, Mendelsohn, & Rubner, 2002), electrical conductivity (Park, Ham, & Grunlan, 2011), anti-flammable (Carosio, Laufer, Alongi, Camino, & Grunlan, 2011;Li et al, 2010;Li, Mannen, Schulz, & Grunlan, 2011), gas barrier Priolo, Gamboa, Holder, & Grunlan, 2010;, and UV resistance (Dawidczyk, Walton, Jang, & Grunlan, 2008). These films, typically < 1µm thick, are created by alternately exposing a substrate to positively-and negatively-charged molecules, polymer electrolytes, or particles, as shown in Figure 12.…”
Section: Nano-modifications Of Textiles Surfaces Using Layer-by-layermentioning
confidence: 99%
“…Increased research interest was shown on TiO 2 due to its unique physicochemical properties, excellent chemical stability, good photo-catalyst, and its ability to protect materials from UV radiation (Zheng et al 2008;Dawidczyk et al 2008;Woan et al 2009). TiO 2 has ability to switch the surface wettability between hydrophilicity and super-hydrophobic (Wang et al 1997;Huang et al 2014;Hoshian et al 2015).…”
Section: Introductionmentioning
confidence: 99%